Pengaruh Literasi Keuangan, Inklusi Keuangan, dan Pembayaran Digital terhadap Kinerja UMKM : Studi Kasus UMKM Kuliner di Kecamatan Boja - Rika Kusuma Wardani; Indriasari, Ika; Nastiti , Prianka Ratri (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to examine the effect of financial literacy, financial inclusion, and digital payment on the performance of culinary MSMEs in Boja District. The research employed a quantitative method with a purposive sampling technique, involving 100 culinary MSME owners. Data were collected using questionnaires with a Likert scale and analyzed through multiple linear regression using SPSS version 25. The results indicate that financial literacy has a positive and significant effect on MSME performance, financial inclusion has a positive but insignificant effect, while digital payment has a positive and significant effect on MSME performance. Simultaneously, the three variables significantly influence MSME performance. This research is expected to serve as an input for MSME actors and related stakeholders to enhance performance through strengthening financial literacy, expanding access to financial inclusion, and optimizing the use of digital payments.